Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance. Issue 3 (May 2015) - Chang, Sue; Krane, Jeffrey F.
<x xml:space="preserve">Abstract</x> Abstract Atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) is the most controversial category in The Bethesda System for Reporting Thyroid Cytopathology. The intent of this category is to recognize a heterogeneous group of cytologic findings that exceed what is acceptable in a benign aspirate while being insufficient to warrant any of the diagnoses associated with a higher risk of malignancy. An AUS/FLUS diagnosis may be prompted by quantitatively or qualitatively restricted features that raise concern for a follicular neoplasm (including a Hürthle cell neoplasm), papillary carcinoma, or other less common malignancies. These aspirates are often limited by factors such as sparse cellularity or preparation artifact. The AUS/FLUS category is anticipated to have a 5% to 15% risk of malignancy, but in practice has been shown to often pose a greater risk, particularly when the atypia is due to cytologic features that raise concern for papillary carcinoma. Recommended initial management for an AUS/FLUS diagnosis is typically repeat fine-needle aspiration with molecular testing presenting a potentially viable alternative for determining whether surgery is appropriate. The AUS/FLUS rate is recommended to not exceed 7%, but this target has proved difficult to achieve for many practitioners. A concerted effort to use alternative diagnostic categories wherever possible may help minimize overuse of AUS/FLUS.